Assistance in Increasing Literacy of Murung Raya Elementary School Students in the Context of Building a Generation of Healthy Character - Jamiatul Hamidah (UMBanjarmasin, 2022)
The purpose of this community service activity is to increase students' interest in reading, especially for educational matters so that students have the provision/knowledge and understanding of the importance of maintaining health, building good character in students, especially loving the natural environment and maintaining cleanliness, and build students' self-confidence. The method of implementing this community service goes through 3 stages, namely planning, implementation, and evaluation. Based on observations of the activities that have been carried out, this activity supports increasing student literacy in order to build a healthy generation of character. This is indicated by changes in knowledge and the impact on student behavior who pay more attention to maintaining health.